Painting in the Laboratory. Scientific examinationfor Art History and Conservation - Gómez González, Marisa (Ge-conservacion, 2015)
Painting in the Laboratory. Scientific examinationfor Art History and ConservationAutora: Karin GroenEditorial: Archetype Publications, 2014Páginas: 200Ilustraciones: 204 en colorISBN: 9781909492134